There are no guard dogs, only a myth about power - Rey Domínguez, Valentina (Re-presentaciones: Periodismo, comunicación y sociedad, 2021)
For decades the journalistic’s myth have been used to explain the profession, to give it meaning, identity and legitimacy, granting it a role in society. Under the ideal of "fourth state power", "watchdog of democracy", the myth has installed ethical values that have ruled the professional practices and attitudes. However, reality shows a distance between that ideal and the journalistic exercise; a dichotomy between myth and practice. The present essay proposes that this problem lies in the myth, in an enunciative construction that theoretically presents a practical impossibility, but that establishes a relation of power that limits and normative journalistic attitudes, installing ethical principles as absolute and doctrinal truths. Therefore, we propose to question the mechanisms production of truth present in the myth; those that establish an order of relations in how the journalist must understand and execute the profession.
Keywords: Myth; True production; Identity